Infant age at egg introduction and malnutrition‐related child growth in the United States. Issue 4 (16th June 2022) - Mi, Baibing; Liu, Huimeng; Wang, Yutong; Small, Hannah; Surguy‐Bowers, Ariana; Rideout, Todd C.; Cameron, Claire E.; Lehman, Heather K.; Starke, Krystal; Wen, Xiaozhong
Abstract: To evaluate the relationship between infant age of egg introduction and malnutrition‐related growth outcomes in the United States, we analysed secondary data of 1716 mother–child dyads in the Infant Feeding Practices Study II and its Year 6 Follow‐Up Study. Malnutrition‐related growth outcomes included body mass index z‐score (BMIZ), obesity (weight‐for‐height z‐score [WHZ] ≥3 or BMIZ ≥ 2), WHZ, wasting (WHZ < −2), height‐for‐age z‐score (HAZ), and stunting (HAZ < –2). Infant age at egg introduction was analysed as a continuous variable. We used generalised estimating equations to estimate the mean difference in continuous outcomes and relative risk [RR]) for binary outcomes, adjusting for related maternal and child confounders. We also explored interactions with child sex, maternal race/ethnicity, maternal educational level, ever breastfeeding, and formula feeding. In the total sample, a later infant age at egg introduction was associated with a lower mean difference in HAZ (confounder‐adjusted mean difference = −0.08, 95% confidence interval [CI]: −0.12 to −0.03 per month) and a higher risk of stunting (confounder‐adjusted RR = 1.17, 95% CI: 1.03–1.33 per month) at 6 years. The associations between infant age at egg introduction and 12‐month growth outcomes differed by child sex. Among females but not among males, later introduction of eggs was associated with a lower mean WHZ (−0.06 [−0.12 to 0.00] per month) at 12 months. Later egg introduction during infancy was associated with a lower mean HAZ and a higher risk of stunting in 6‐year‐old children. Besides this, it was associated with a lower WHZ among females at 12 months. Abstract : Later egg introduction during infancy was associated with a lower mean height‐for‐age z‐score (HAZ) and a higher risk of stunting in 6‐year‐old children. Besides this, it was associated with a lower weight‐for‐height z‐score (WHZ) among females at 12 months. Key messages: This secondary data analysis evaluated the relationship between infant age at egg introduction and malnutrition‐related growth outcomes among young US children within the Infant Feeding Practices Study II and its Year 6 Follow‐up Study. In the total sample, a later infant age at egg introduction was associated with a lower mean 6‐year height‐for‐age z‐score and a higher risk of stunting at 6 years. The associations between infant age at egg introduction and 12‐month growth outcomes differed by child sex. Later introduction of eggs was associated with a lower mean weight‐for‐height z‐score among females. However, this association was not observed among males.